2019
DOI: 10.1097/rlu.0000000000002768
|View full text |Cite
|
Sign up to set email alerts
|

Early-Phase 18F-Florbetaben PET as an Alternative Modality for 18F-FDG PET

Abstract: Purpose Based on the possibility that early-phase florbetaben (E-FBB) brain PET can be a surrogate for brain perfusion imaging, we conducted this study to investigate the clinical utility of E-FBB PET instead of 18F-FDG brain PET. Materials and Methods This prospective study included 35 patients with clinical suspicion of cognitive decline or dementia and 5 healthy controls. Brain MRI, E-FBB PET, late-phase FBB PET, and FDG PET were acquired. The region… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 29 publications
2
26
1
Order By: Relevance
“…Most previous studies that reported the usefulness of early-phase 18 F-FP-CIT or amyloid PET performed validation with 18 F-FDG PET 15 , 19 23 or 15 O-water perfusion PET 24 , but our study did not. Patients included in our retrospective study did not undergo 18 F-FDG or perfusion PET imaging, so we cannot validate that early-phase PETs in our study reflect true brain perfusion.…”
Section: Discussioncontrasting
confidence: 62%
See 1 more Smart Citation
“…Most previous studies that reported the usefulness of early-phase 18 F-FP-CIT or amyloid PET performed validation with 18 F-FDG PET 15 , 19 23 or 15 O-water perfusion PET 24 , but our study did not. Patients included in our retrospective study did not undergo 18 F-FDG or perfusion PET imaging, so we cannot validate that early-phase PETs in our study reflect true brain perfusion.…”
Section: Discussioncontrasting
confidence: 62%
“…In our study, 18 F-flutemetamol was used as a radiopharmaceutical for amyloid PET. Previous studies that reported the usefulness of early-phase imaging with amyloid PET have used 11 C-Pittsburgh Compound B 19 , 22 , 24 , 27 , 28 , 18 F-florbetapir 20 , 23 , or 18 F-florbetaben 15 , 18 , 28 , 29 , and we could find only single previous report using 18 F-flutemetamol 26 . Since this study was carried out retrospectively, we could not select the radiopharmaceuticals used for amyloid PET.…”
Section: Discussionmentioning
confidence: 77%
“…In this study, FMFs were acquired with the three approved and commercially available 18 F-labeled amyloid tracers, namely [ 18 F]FBP, [ 18 F]FBB, and [ 18 F]FMM [ 8 ]. Whereas early-phase amyloid PET images have been evaluated in various studies as a surrogate for cerebral metabolism using [ 18 F]FBP [ 22 , 23 , 24 , 25 , 26 , 27 ] and [ 18 F]FBB [ 19 , 28 , 29 , 30 , 31 ], no study comparing early-phase amyloid PET acquisitions with [ 18 F]FMM to [ 18 F]FDG PET images was found during the writing of this manuscript. However, the optimal time windows for the acquisition of dual-phase [ 18 F]FMM PET images are being investigated [ 32 ] in addition to its perfusion information [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a slight increase of correlation coefficients in Aβ+ patients compared to Aβ− patients can be observed in our study despite not showing statistically significant differences, similarly to the results of Daerr et al However, a statistically significant difference in the [ 18 F]FMM subcohort indicates higher correlation coefficients in the Aβ− group. Additionally, Son et al [ 31 ] obtained correlation coefficients reaching r = 0.8752 in the left temporal lobe, comparing static 5-min early [ 18 F]FBB PET images to [ 18 F]FDG PET. In our study, the [ 18 F]FBB FMF shows a correlation of r = 0.91 in the left temporal VOI to [ 18 F]FDG PET.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation